Late Sophocles The Hero's Evolution in Electra, Philoctetes, and Oedipus at Colonus - Van Nortwick, Thomas (University of Michigan Press, 2015)
"Only a few plays by Sophocles-one of the great tragic playwrights from Classical Athens-have survived, and each of them dramatizes events from the rich store of myths that framed literature and art. Sophocles' treatment evokes issues that were vividly contemporary for Athenian audiences of the Periclean age: How could the Athenians incorporate older, aristocratic ideas about human excellence into their new democratic society? Could citizens learn to be morally excellent, or were these qualities only inherited? What did it mean to be a creature who knows that he or she must die? Late Sophocles traces the evolution of the Sophoclean hero through the final three plays, Electra, Philoctetes, and Oedipus at Colonus. The book's main thesis, that Sophocles reimagined the nature of the tragic hero in his last three works, is developed inductively through readings of the plays. This balanced approach, in which a detailed argument about the plays is offered in a format accessible to nonspecialists, is unusual-perhaps unique-in contemporary Classical scholarship on Sophocles. This book will appeal to nonspecialist readers of serious literature as well as scholars of classical and other literatures. While including ample guidance for those not familiar with the plays, Late Sophocles goes beyond a generalized description of "what happens" in the plays to offer a clear, jargon-free argument for the enduring importance of Sophocles' plays. The argument's implications for longstanding interpretational issues will be of interest to specialists. All Greek is translated."